Discontinued Maternal Health Care Utilization in Bhojpur District, Nepal - Dulal, Komal Prasad (Intellectual Inception: A Multidisciplinary Research Journal of Bhojpur Campus, 2024)
Why all pregnant women did not receive all care at antenatal period; those who did not even utilize any ANC visit may also prefer to utilize facility-based delivery or postnatal care related queries are rarely available in several rounds of NDHS data set. A study conducted in Tarai region of Nepal, analysis of Nepal demographic and health surveys of several rounds, Annual Health Report 2077/78 published by the Department of health services, Ministry of health and population were taken into study. A qualitative study designed in 2014-15 from the women of reproductive health having children of 2-23 months were asked their discontinuation, if any. Maternal health service utilization through national and the district level data were analysed to study about the discontinuation in utilization.Several factors are identified as the cause for discontinuation in the Tarai region of Nepal. Data revealed by department of health services for the fiscal year 2077-78 show discontinued maternal health service utilization (MHSU) in Bhojpur district. The NDHS 2022 report still found some level of discontinuation in national level. Therefore, urgent need of qualitative study is a most for Bhojpur district which has low level of utilization. In the new administrative set-up according to constitution of Nepal, effective functional policy adopted by municipal region may solve several issues of maternal health. Hilly regions could have different response than Tarai region of Nepal. Therefore, local bodies of hilly regions should bring maternal health policy and program to achieve continuum of maternal health care which will ultimately help Nepal to achieve SDG related goal and target.